The impact of agricultural credit on the cattle inventory and deforestation in Colombia: A spatial analysis - Mejia Tejada, Daniela; Díaz Baca, Manuel Francisco; Enciso Valencia, Karen Johanna; Bravo Parra, Aura Maria; Florez, Jesus Fernando; Junca Paredes, John Jairo; Burkart, Stefan (Springer, 2024)
The relationship between agricultural credit and agricultural production as well as the impacts on sustainable development (i.e., poverty alleviation, reduction of inequalities, food and nutrition security, and stimulation of economic growth) have been widely documented. The objective of this study is to analyze the impact of credit on cattle production and deforestation in Colombia through spatial panel data models. For this purpose, a departmental data panel for the period 2011–2020 was built, based on available information from public entities. The results suggest that in Colombia, the relationship between access to credit and cattle production is significant and can be either negative or positive. In addition, there is evidence of spatial dependence, meaning that cattle production in one department is being affected by cattle production in a neighboring department or by all the departments that make up the national territory. Regarding deforestation, results show that, although the number of cattle present in a department does affect its annual deforestation rate due to a poor coverage of sustainably intensified cattle ranching systems, there is no relationship between deforestation and the access to credit nor any spatial correlations.